2020
DOI: 10.1080/1540496x.2020.1787151
|View full text |Cite
|
Sign up to set email alerts
|

Which Firm-specific Characteristics Affect the Market Reaction of Chinese Listed Companies to the COVID-19 Pandemic?

Abstract: This paper investigates market reaction to the novel corona virus (COVID-19) pandemic. Using a sample of Chinese listed firms, we find that market reaction to the COVID-19 outbreak is more intense in firms within the industries that are vulnerable to the virus, and those with high institutional investors. Furthermore, firms with larger scale, better profitability and growth opportunity, higher combined leverage, and less fixed assets experience less adverse impact of the COVID-19 outbreak than other firms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
119
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(134 citation statements)
references
References 16 publications
10
119
4
1
Order By: Relevance
“…They find that the impact of COVID-19 varies across different industries, ownership structure, and firm size. Shen, Fu, Pan, Yu, and Chen (2020) and Xiong, Wu, Hou, and Zhang (2020) examine the reaction of Chinese listed stocks to the lockdown in Wuhan due to the COVID-19 outbreak and find that the impact varies across different industries, firm size, profitability, growth opportunity, leverage, and fixed assets. They also find that the negative impact of COVID-19 on firm performance is more pronounced in China’s regions with high confirmed cases of COVID-19 and specific industries that were adversely affected by COVID-19.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…They find that the impact of COVID-19 varies across different industries, ownership structure, and firm size. Shen, Fu, Pan, Yu, and Chen (2020) and Xiong, Wu, Hou, and Zhang (2020) examine the reaction of Chinese listed stocks to the lockdown in Wuhan due to the COVID-19 outbreak and find that the impact varies across different industries, firm size, profitability, growth opportunity, leverage, and fixed assets. They also find that the negative impact of COVID-19 on firm performance is more pronounced in China’s regions with high confirmed cases of COVID-19 and specific industries that were adversely affected by COVID-19.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…With reference to the influence of the pandemic on the enterprise's activities, Mazur, et al [79] contended that companies reply in various means to the COVID-19 revenue shock because many sectors were locked throughout the quarantine stage. Hence, Xiong, Wu, Hou and Zhang [9] evidenced that companies belonging to sectors that are exposed to the pandemic have significantly lower cumulative abnormal returns, but enterprises with good financial conditions endure less opposing effect of the disease. Nguyen [80] established that energy segment experienced the utmost abnormal negative returns amid all sectors.…”
Section: Prior Research Regarding the Economic And Financial Consequementioning
confidence: 99%
“…In other words, we examine whether market volatility at the Asian regional level can explain stock market volatility at the country-level. Recent studies have shown that the COVID-19 pandemic has significantly affected global economies; see, for instance, Mishra et al (2020), Salisu & Akanni (2020), Chen et al (2020), Wang et al (2020), Yue et al (2020), Yu et al (2020), Xiong et al (2020), Shen et al (2020), Gu et al (2020), Haroon & Rizvi (2020), Iyke (2020), He et al (2020), and Liu et al (2020). According to Sha & Sharma (2020) and Phan & Narayan (2020), the COVID-19 pandemic represents the largest and most disturbing shock to the global economic system and it is therefore important to understand whether the country level volatility can be determined by the regional level stock market volatility.…”
Section: Introduction I Introductionmentioning
confidence: 99%